Dynamic behavior of new aluminum–steel energy dissipating devices. Issue 7 (6th March 2013) - Foti, Dora; Diaferio, Mariella; Nobile, Riccardo
SUMMARY In the present study, a new dissipation device for seismic protection of structures is proposed. This device is designed to dissipate the energy entering a structure during an earthquake through the activation of hysteretic loops of an aluminum plate located in the middle of the device itself. To maximize the amount of dissipated energy, we performed the design of the device requiring that the aluminum plate is stressed in an almost uniform way. In particular, the device is designed to concentrate energy dissipation in the aluminum core, whereas the external steel plates are dimensioned to give an adequate stiffness to the device and to limit instability phenomena. Characterization tests have been performed on two typologies of device designed for different levels of the maximum shear force (20 and 40 kN, respectively). Moreover, to verify the behavior of the aluminum–steel device, we performed characterization tests on the aforementioned devices realized without the aluminum plate. The results show that the steel plates behave elastically in the range of forces expected in the device during an earthquake, confirming that the aluminum plate is the main element for the hysteretic energy dissipation. Copyright © 2013 John Wiley & Sons, Ltd.